PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN LIKUIDITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN PERIODE 2013-2017 - Putri Triana Meissy; Desmiyawati Desmiyawati; Safitri Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of The Effect Of Profitability, Leverage,Firm Size, Firm age and Liquidity on timeliness of financial reporting. The populations inthis study are 41 mining companies listed in the Indonesia Stock Exchange (IDX) duringthe period 2013-2017. The research method used in this study is a quantitativemethod which aims to test the relationships between variables through testinghypotheses by using 65 observation in 13 companies for five periods. The sampleselection method uses purposive sampling in mining companies listed in theIndonesia Stock Exchange during the 2013-2017 periods. Hypothesis testingtechniques are carried out using logistics analysis using the SPSS program. Theresults of the research show that 1) there are positive and significant effects ofprofitability on timeliness of financial reporting, 2) leverage have no significanteffect on timeliness of financial reporting, 3) there are positive and significanteffects of firm size on timeliness of financial reportin , 4) firm age has positive andsignificant effects on timeliness of financial reporting, 5) liquidity have nosignificant effect on timeliness of financial reporting.Keywords: Timeliness, Profitability, Leverage, Firm Size, Firm Age, Liquidity